High-spin states and deformation properties in 187Pt - Cardona, Maria Angelica (2007)
High-spin states in 187Pt have been studied by means of γ-ray spectroscopy techniques. Known bands have been significantly extended and new bands have been found. The band structures are briefly discussed.